The effects of the COVID-19 pandemic on the well-being of children with autism spectrum disorder: Parents’ perspectives - Amirova, Aida; CohenMiller, Anna; Sandygulova, Anara (Frontiers in Psychiatry, 2022)
The COVID-19-related lockdown interrupted children's learning progress and discontinued social learning and regular activities that children with ASD rely on socially and physically. Negative consequences for children with ASD were reported far and wide. To investigate this problem in Kazakhstan, we conducted a mixed-methods study that drew on data from an online survey with 97 parents and semi-structured interviews with 14 parents. While parent-report quantitative results suggest that children were likely to experience negative impacts of the pandemic due to disrupted educational and therapeutic services, qualitative findings confirm that they have experienced elevated mental health and behavioral challenges during the lockdown. Remote educational and therapeutic services were not helpful as families coped with pandemic-caused problems on their own. We highlight that continued support and care during and after a crisis is vital not only for children with ASD but also for the families under-resourced mentally and socially.